Percutaneous microcoil localization as an aid to ultrasound-guided hepatic gastrointestinal stromal tumor metastasis resection: A case report - Ravjot Dhatt; Leandro Cardarelli-Leite; Sonia Butterworth; Manraj Heran (Elsevier, 2023)
Introduction: Liver nodules that develop in children with cancer may represent primary malignancy, metastatic disease, or other conditions potentially requiring aggressive management. Laparoscopic methods have been utilized for nodule resection with perioperative ultrasonographic assistance. However, certain nodules in liver tissue can be difficult to identify on ultrasonography. Ultrasonography guided surgical resection after computer tomography (CT)-guided localization using microcoils is an innovative technique that has the potential to assist in the resection of small or deep liver nodules in children in these unique cases. Case presentation: A 15-year-old female presented with evidence of a hypermetabolic liver nodule on routine PET scan, 5 years following resection of a hepatic metastasis via right hepatic trisegmentectomy for primary gastrointestinal stromal tumor (GIST). Contrast-enhanced CT confirmed presence of a new suspicious liver nodule. Given the interval from initial treatment to the identification of this hepatic nodule, consent was received from patient and her family to surgically resect the nodule. However, pre-operatively the nodule could not be appreciated on ultrasonography. Interventional radiology was consulted for CT guided percutaneous microcoil localization of the hepatic nodule. CT-guided percutaneous microcoil localization with ultrasonographic guided liver resection allowed for complete resection of the liver nodule. Conclusion: We have successfully used an innovative technique of CT-guided microcoil placement to direct ultrasound-guided surgical resection of an otherwise ultrasound-occult liver nodule in the pediatric setting.